PROFESSIONALISM AND COMPENSATION IN IMPROVING JOB SATISFACTION - Wardoyo, Cipto (Universitas Brawijaya, Indonesia, 2017)
The act number 14 year 2005 on Teachers and Lecturers, is a new era for the teaching profession; because the teacher is a professional job that requires different competencies that must be mastered. These competencies are include pedagogical competence, personality, social, and professional; then called variables professionalism of teachers, which will determine the job satisfaction of teachers. Related with job satisfaction of teachers, compensation is also a variable that is important in determining the level of job satisfaction, and compensation will be measured by indicators of intrinsic and extrinsic translated into several indicators of compensation financial reward, interpersonal rewards and a sense of completion, recognition and autonomy, and the promotion, achievement and growth. The level of job satisfaction related to characteristics of the job, a job that requires the completion of the high level of complexity, of the work requires concentration, skill and expertise that will provide satisfaction are different compared to a job that does not require the mind, high craftsmanship. This study aimed to analyze the influence of teacher professionalism and compensation to job satisfaction partially, as well as to test the research hypothesis. In this research a population of 132 teachers of economic subjects /Accounting High School in Malang City, samples taken 66 (50%) with incidental sampling technique.The analysis technique used is multiple regression techniques, which is preceded by the classical assumption. The analysis showed that the variables of professionalism and teacher compensation partially significant effect on job satisfaction of teachers; and the dominant influence on job satisfaction variables are variables professionalism which means that also the hypothesis that this study received a hypothesis that has been formulated.